Usability Evaluation of i-Saku Mobile Application Using Usability Testing Method With PACMAD Model - Charvia Cipta Wijaya (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
The i-saku application is a digital wallet or money app published by PT Inti Dunia Sukses and used for transactions at Indomaret. Currently, the i-saku app has a low rating and many negative user reviews on the Google Play Store. In this study, the PACMAD model was used to test seven usability attributes: Effectiveness, Efficiency, Satisfaction, Learnability, Memorability, Error, and Cognitive Load. Data was collected through three techniques: Performance Measurement, System Usability Scale (SUS), and Retrospective Think Aloud (RTA). The research findings showed an effectiveness rate of 85.33% for the i-saku app, an efficiency rate of 0.04398689 goals/second, a satisfaction rate of 43, good learnability and memorability levels, an error rate of 0.026, and 26 complaints regarding cognitive load. This study provides information on the usability evaluation of the i-saku app using the PACMAD model and offers suggestions for improvement based on the findings